Mainstream avenues for boosting graphitic carbon nitride efficiency: towards enhanced solar light-driven photocatalytic hydrogen production and environmental remediation. Issue 21 (20th May 2020) - Lam, Su Shiung; Nguyen, Van-Huy; Nguyen Dinh, Minh Tuan; Khieu, Dinh Quang; La, Duc Duong; Nguyen, Huu Trung; Vo, Dai Viet N.; Xia, Changlei; Varma, Rajender S.; Shokouhimehr, Mohammadreza; Nguyen, Chinh Chien; Le, Quyet Van; et al.
Abstract : This review endeavors to present a roadmap to prepare high-performance g-C3 N4 photocatalysts for hydrogen production and environmental remediation. Abstract : Photocatalysts comprising 2D carbon nitride-based systems have emerged as a fervently researched topic for addressing the problems of fuel depletion and the environment. However, the photocatalytic activities of pristine g-C3 N4 are still mediocre and suffer from issues pertaining to the restrictions in light absorption, charge separation, and carrier-induced surface reactions; however, efforts have been made in the past decades to boost the efficiencies. This review endeavors to present a roadmap to prepare high-performance g-C3 N4 photocatalysts by expounding the cutting-edge research on g-C3 N4 materials either as a single component or g-C3 N4 -based composites including current challenges and perspectives on this topical theme. We believe that this review will provide a broader picture and recommendations for the preparation of superior g-C3 N4 photocatalysts towards a greener, cleaner, and resilient future.